2020
DOI: 10.1159/000510313
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of the Recommendations for Patients with Pollen Allergies and Evaluation of Their Scientific Relevance

Abstract: Pollens are responsible for allergic rhinitis, conjunctivitis, and asthma. The incidence of these diseases, which have adversely impacted the social and professional lives of people who are allergic to pollen, has tripled in the past 25 years. Official institutes, health care institutions, public interest groups, and mainstream news media provide people who are allergic to pollen with advice aimed at reducing their symptoms. The aim of this work was to provide an inventory of the prevention guidelines in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 90 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…The important role of human behavior in pollen diffusion and/or retention has also been evidenced by experimental studies, where a mean of 0.93% of the initial pollen load was retained after a single wash of hands and traces of several species were found after numerous hand-wash cycles [84]. Moreover, the knowledge of pollen hourly peaks creates the opportunity to plan appropriate preventive measures and recommendations, addressed mainly to the sensitization of workers [85].…”
Section: Discussionmentioning
confidence: 92%
“…The important role of human behavior in pollen diffusion and/or retention has also been evidenced by experimental studies, where a mean of 0.93% of the initial pollen load was retained after a single wash of hands and traces of several species were found after numerous hand-wash cycles [84]. Moreover, the knowledge of pollen hourly peaks creates the opportunity to plan appropriate preventive measures and recommendations, addressed mainly to the sensitization of workers [85].…”
Section: Discussionmentioning
confidence: 92%
“…While all of these procedures are based on common sense, they have not been clinically validated [124]. This paper demonstrated that four recommendations are provided by most scientific committees and organizations: avoiding outdoor activities, consulting pollen forecasts, avoiding drying laundry outdoors, and wearing pollen protective glasses and mask when outdoors.…”
Section: Individual Avoidance Proceduresmentioning
confidence: 99%
“…A great deal of the focus on allergy management rightly focuses on avoiding the outdoors and strategies to prevent pollen from entering indoors [16]. Yet, it is inevitable that pollen will enter the home, and additional research concerning indoor management is still valuable.…”
Section: Introductionmentioning
confidence: 99%